Cognitive performance in juvenile myoclonic epilepsy patients with specific endophenotypes. (August 2016) - Carvalho, Kelly Cristina de; Uchida, Carina Gonçalves Pedroso; Guaranha, Mirian Salvadori Bittar; Guilhoto, Laura Maria F.F.; Wolf, Peter; Yacubian, Elza Márcia Targas
Highlights: Absence of specific precipitant factors in JME indicates a better cognitive performance. Reflex traits in JME relate to myoclonia persistence, polytherapy, and psychiatric comorbidity. A combination of reflex traits associates with greater dysexecutive syndrome. Abstract: Purpose: Juvenile myoclonic epilepsy (JME) is a heterogeneous syndrome in which seizures can be precipitated not only by non-specific factors, such as sleep deprivation and stress, but also by specific stimuli, such as photic stimuli, eye-closure, praxis, and language. The presence of these reflex traits may indicate the hyperexcitability of different cortical areas, which may be reflected in patients' neuropsychological deficit profile. The objective of our study is to investigate the possible relations between JME endophenotypes and patients' cognitive performance. Methods: 61 JME patients were divided into four groups: no reflex traits (group 1, 20 patients); praxis induction (group 2, 13); eye-closure and/or photosensitivity (group 3, 17); and a combination of different reflex traits (group 4, 11). Neuropsychological performance was compared between JME subgroups. 60 healthy controls were used to calculate z -scores. Patients also underwent psychiatric assessment. We controlled the clinical variables, e.g. age at epilepsy onset, frequency of myoclonic seizures, total and sedative drug load, setting them as covariables for the ANOVA analysis. Results: Praxis induction was more common in males ( p  = 0.018) and groups with reflex traits (2, 3, and 4) presented higher rates of persistent myoclonia, polytherapy, clonazepam use (group 3), and more frequent psychiatric comorbidities. Group 4 patients performed worse in Trail Making Test B than the patients in group 1. These findings were independent of clinical variables. Conclusion: JME patients with a combination of praxis induction and eye-closure/photosensitivity had greater executive dysfunction, revealing an association between reflex ictogenic mechanisms and cognitive performance.